Designing NSM FRP systems in concrete using partial safety factors - Coelho, Mário; Neves, Luís C.; Sena-Cruz, José (Elsevier, 2018)
This paper presents design procedures for fibre reinforced polymer (FRP) systems inserted in the cover of concrete elements according to the near-surface mounted (NSM) technique. Such strengthening system depends greatly on their bond strength. Two existing design formulations to estimate the bond strength of NSM FRP systems in concrete are studied. A reliability analysis is conducted with the purpose of making the design formulations consistent with the partial safety factors philosophy, including the Eurocodes. Hence, the necessary probabilistic distributions are calibrated based on a large database of bond tests. The results presented herein show that the existing guidelines can be extended and adopted under the framework of the Eurocodes. However, mainly due to their limitations in addressing individually all the possible failure modes, the variability of the probabilistic distributions found are quite high, leading to high partial coefficients of safety. Thus, in the future, new and improved formulations should be developed.